Gamification as a strategy for planning Mathematics classes (Unnes Journal of Mathematics Education Research, 2022)
This work presents the results of a workshop carried out with students of the Mathematics Licentiate Course at the State University of Ceará, Brazil, dealing with gamification in the teaching of Mathematics and pointing out the relevance of its incorporation into the teaching methodology. The objective of this work was to build a set of educational games aimed at the gamification of curricular components of the mathematics discipline using the Wordwall platform, based on a class plan carried out by the scholarship holders, aiming to add the use of technology in teaching to their academic training. The methodology is an exploratory research, action-research type, where students actively participated in a workshop on the platform, its dynamics, available materials, and formats. From the first contact with Wordwall, the students performed as an activity a lesson planning using gamification with Wordwall, using as themes curricular components of the mathematics discipline.